Utilizing Knowledge of Physics in Safety Engineering - Jiri Svec; Radomir Scurek; Pavel Svec (Communications - Scientific letters of the University of Zilina, 2011)
Any technician working in safety engineering needs certain knowledge of physics. This knowledge includes physical quantities and units of measurement, physical properties of substances, various formulae and equations, etc. It is also very important to possess knowledge enabling general – and often highly complex – processes to be simplified. This paper discusses two such possibilities for simplification.